THE ROLE OF DIGITAL LITERACY IN ENHANCING SME ENTREPRENEURIAL PERFORMANCE : A Literature Review - R. Meutia Fransiska; Ritha F Dalimunthe; Prihatin Lumbanraja (Cahaya Ilmu Bangsa, 2024)
Small and medium-sized enterprises (SMEs) are crucial contributors to economic growth worldwide. Yet, they often face considerable challenges in fully utilizing digital technologies. This extensive literature review explores the complex relationship between digital literacy and SME entrepreneurial performance across varied global environments. It examines a range of studies highlighting how digital literacy enables SMEs to innovate, integrate e-commerce solutions, enter new markets, and enhance their overall business performance. The review highlights the intricate digital landscape SMEs navigate, marked by regional differences, sector-specific challenges, and the continuous evolution of digital skill needs. The goal of this study is to offer practical recommendations for policymakers and organizations supporting SMEs, suggesting focused measures to bridge the digital skill divide. By improving digital literacy among SMEs, we can unlock their potential, boosting entrepreneurial success and contributing to sustainable economic growth globally.